Effects of Pandemic on Feelings of Depression in Italy: The Role of Age, Gender, and Individual Experiences During the First Lockdown - Arpino, Bruno; Pasqualini, Marta (Frontiers in Psychology, 2021)
The restrictions to physical contacts, that have been imposed in different countries to deal with the COVID-19 pandemic, may have contributed to an increase in feelings of depression on top of other negative consequences of the pandemic. This paper examines the consequences of the COVID-19 pandemic on feelings of depression by using original data collected in Italy between 14-24 April 2020. Quota sampling (N = 3,026) was used to target the population 18+ and together with post-stratification weights permitted obtaining a representative sample of the Italian population with respect to key socio-demographic factors. We find that about 50% of respondents felt sad or depressed more often than usual. Adopting a life-course perspective we revealed a great heterogeneity of feelings of depression consequences by age, gender and difficulties experienced during the first national lockdown. Identifying population’s groups at higher risk of suffering from feelings of depression as a result of COVID-19 is crucial to limit indirect long-term consequences of the pandemic.